2021
DOI: 10.1021/acs.energyfuels.0c02961
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Modeling of Subsurface Phenomena Related to Petroleum Engineering

Abstract: Experiments are always the go-to approach to reveal mysterious observations and verify new theories. However, scientific research has shifted to areas that are difficult to probe experimentally. Fortunately, computational approaches, such as molecular simulation, became available. With a rigorous theoretical foundation and microscopic insights, molecular simulation could explore unknown territories in physics and validate macroscopic theories. Grand challenges in petroleum engineering require knowledge at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 165 publications
0
10
0
Order By: Relevance
“…However, LSE mechanisms relevant to liquid–liquid interactions are still needed to be further investigated, especially for osmotic effect, microdispersion, and snap-off. Therefore, multiple disciplines theory should be utilized to account for these phenomena, including interfacial chemistry. Although MD simulation has been successfully applied to LSW, only focus one single crude oil component and one pure mineral. ,,, Therefore, MD simulation results are suggested based on neglecting the collaborate effects of minerals and brine compositions on LSW. In addition, experimental research should be done to verify the accuracy of MD simulation.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, LSE mechanisms relevant to liquid–liquid interactions are still needed to be further investigated, especially for osmotic effect, microdispersion, and snap-off. Therefore, multiple disciplines theory should be utilized to account for these phenomena, including interfacial chemistry. Although MD simulation has been successfully applied to LSW, only focus one single crude oil component and one pure mineral. ,,, Therefore, MD simulation results are suggested based on neglecting the collaborate effects of minerals and brine compositions on LSW. In addition, experimental research should be done to verify the accuracy of MD simulation.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Although MD simulation has been successfully applied to LSW, only focus one single crude oil component and one pure mineral. ,,, Therefore, MD simulation results are suggested based on neglecting the collaborate effects of minerals and brine compositions on LSW. In addition, experimental research should be done to verify the accuracy of MD simulation.…”
Section: Challenges and Perspectivesmentioning
confidence: 99%
“…Molecular simulation is a computational chemistry method developed with the advance of computer technology and quantum chemistry to study the microscopic properties of molecules from the atomic level. , In order to make molecular dynamics simulations of large-scale chemical reaction systems practical, Van Duin et al developed a reaction force field (ReaxFF) system and it was shown that ReaxFF calculations are faster and the results are more accurate for small-molecule hydrocarbons. This also officially opened the application of ReaxFF method in the field of hydrocarbon microreactions.…”
Section: Introductionmentioning
confidence: 99%
“…Nonbonded parameters include Coulomb and van der Waals forces, which are commonly calculated using a Lennard-Jones potential to allow nonbonded particles to escape an equilibrium distance with diminishing energy penalties that may be overcome by other, stronger forces . These force field parameters are also used in other calculations, such as Monte Carlo simulations , E normalt normalo normalt normala normall = normalb normalo normaln normald normals K r ( r r e q 2 ) + normala normaln normalg normall normale normals K θ false( θ θ eq false) 2 + normald normali normalh normale normald normalr normala normall normals V n 2 [ 1 + cos false( n ϕ γ false) ] + i < j true[ A italicij R italicij 12 B ij R ij 6 + q i q j ϵ R italicij ] …”
Section: Introductionmentioning
confidence: 99%